SISTEM PENUNJANG KEPUTUSAN LAPORAN KEUANGAN UMKM PEDAGANG SEMPOL MENGGUNAKAN METODE SIMPLE ADDICTIVE WEIGHTING (SAW) APLIKASI MATLAB STUDI KASUS: SEMPOL NENG RIVANI - Sultan Aji Saputra; Aisyah Mawar Kusuma Salsabila; Muhmmad Nur Ikmalul Ilmi; Roeslan Djutalov (CV. Multi Kreasi Media, 2024)
This study aims to develop a decision support system using the Simple Additive Weighting (SAW) method for the financial reports of sempol traders. Financial statements are an important component in measuring the financial performance of a company, including MSMEs. However, in many cases, pimp traders face difficulties in effectively analyzing and evaluating their financial reports. The SAW method is used in this study because it can provide the right solution to overcome this problem. This method involves structured steps in processing and comparing various relevant factors in the financial statements of sempol traders. These factors include revenue, operating costs, net profit, and others. Each factor is given a weight according to the level of importance in decision making.In this study, a decision support system was developed using the latest programming languages and technologies. This system allows sempol traders to upload their financial statements, which will then be processed by the SAW method. The result is a relative ranking of each financial statement based on predetermined factors. Sempol traders can use this information to evaluate their financial performance, identify weaknesses and strengths, and make better decisions in managing their business. This research has the potential to make a significant contribution to sempol traders in improving their understanding of financial statements and in making data-driven decisions. With this SAW-based decision support system, it is hoped that sempol traders can manage their finances more effectively and improve overall business performance